The proficiency levels of college freshmen in the University of the Philippines for college mathematics, 1961-1962 - Gonsalves, Corazon Y. 1926- ([Quezon City s.n.], 1961)
The purpose of this study was to determine the college mathematics proficiency levels of college freshmen who are enrolled in the University of the Philippines for the school year, 1961-1962.
Thesis (M.Ed.)--University of the Philippines.
Keywords: University of the Philippines -- Students; Mathematics -- Study and teaching (Secondary).